CEA and Cyfra 21-1 linked to serial miRNA expressions of advanced-stage non-small cell lung cancer in Indonesia - Hanafi, Arif Riswahyudi; Jayusman, Achmad Mulawarman; Imelda, Priscillia; Alfasunu, Serafim; Sadewa, Ahmad Hamim; Pramono, Dibyo; Heriyanto, Didik Setyo; Haryana, Sofia Mubarika; Kresno, Siti Boedina (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2023)
Globally, lung cancer is one of the cancers leading to dead, dominated by non-small cell lung cancer (NSCLC). In a previous study has shown those serial miRNA expressions (miR-148, miR-34, miR-222, and miR-155) had prognostic value in advanced-stage NSCLC patients. Meanwhile, CEA and Cyfra 21-1, pulmonary tumor markers, are sometimes considered in the Department of Pulmonology, Dharmais Cancer Hospital, Jakarta, although they are not used in routine clinics for prognostication. Both miRNA and CEA-Cyfra 21-1 are valuable biomarkers in NSCLC. This study aimed to evaluate their correlation between CEA and/or Cyfra 21-1 with miRNA expressions in NSCLC patients. It was a cohort retrospective study using data from the previous study. The correlation between variables was analyzed by Spearman-rho. A positive correlation was observed between CEA and Cyfra 21-1 with miR-148, miR-222, and miR-155 [(CEA: p=0.00369, r=0.522; p=0.00242, r=0.542; p 0.00106, r=0.576) (Cyfra: 21-1= p 0.01252, r=0.378; p=0.00035, r=0.519; p=0.01532, r=0.368)]. In conclusion, CEA and Cyfra 21-1 correlate with miR-148, miR-222, and miR-155 expressions in advanced-stage NSCLC.